2020
DOI: 10.1093/iwc/iwaa009
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Intention: The Impact of General Computer Self-Efficacy and Computer Anxiety

Abstract: Entrepreneurs are valuable assets because of their enormous contribution to their nations’ economy through creating new ventures and job opportunities. The entrepreneurship literature is informative with respect to what drives individuals to become entrepreneurs. However, it does not shed light on IT-related factors that can explain and predict entrepreneurial intention. The current study investigates the technological perspective and develops a theoretical model that extends the theory of planned behavior (TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The conditional indirect effects of learning motivation on entrepreneurial intention were significant at low, mean and high levels of the moderator technological selfefficacy, mediated through human capital, thus supporting H5. The results broadly support existing studies pointing at the role of technological self-efficacy in enhancing entrepreneurial intention (Albashrawi and Alashoor, 2020;Chen, 2014;Chen, 2019;Dang et al, 2016). It should be noted that the interaction of technological self-efficacy in the second stage (human capital to entrepreneurial intention) was not significant.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The conditional indirect effects of learning motivation on entrepreneurial intention were significant at low, mean and high levels of the moderator technological selfefficacy, mediated through human capital, thus supporting H5. The results broadly support existing studies pointing at the role of technological self-efficacy in enhancing entrepreneurial intention (Albashrawi and Alashoor, 2020;Chen, 2014;Chen, 2019;Dang et al, 2016). It should be noted that the interaction of technological self-efficacy in the second stage (human capital to entrepreneurial intention) was not significant.…”
Section: Discussionsupporting
confidence: 89%
“…Self-efficacy theory and the findings from previous studies hint at the influential role of selfefficacy in determining the intention to engage in entrepreneurship (Albashrawi and Alashoor, 2020;Chen, 2014;Chen, 2019). Self-efficacy, "mobilizes the motivation, cognitive Fostering entrepreneurial mindsets resources, or courses of action needed to successfully execute a specific task within a given context" (Stajkovic and Luthans, 1998, p. 66).…”
Section: Conditional Indirect Effect Of Technological Self-efficacymentioning
confidence: 91%
See 1 more Smart Citation
“…Theory of planned behavior has been widely used in IS research. It has been regarded a very popular model because; 1) its capacity to provide a good explanation to people's social behavior (Ajzen 2011); and 2) its reliable generalizability across different disciplines, for instance, in education (Iakovleva et al 2011;Pihie and Bagheri 2013), healthcare (Rashidian & Russell 2011;Sivell et al 2013), consumer behaviors (Weisheng et al 2014), mobile commerce (Mishra 2014), and entrepreneurship (Albashrawi and Alashoor, 2020).…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Some of the studies found students who always have a positive judgment about using computers and The Influence of Computer and Internet Self-Efficacy on Individual Entrepreneurial Orientation: An Empirical Study among Bumiputra University Students in Malaysia searching the internet for information lead them to high ICT self-efficacy. Computer self-efficacy can be explained as a person'sjudgment on their competency in using various computer applications (Albashrawi & Alashoor, 2017); meanwhile, internet self-efficacy is an individual's belief on his or her ability to utilize functions of the internet (Hsu & Chiu, 2004). Computer and the internet self-efficacy are the two (2) important element that complements each other that should be acquired by entrepreneurs, in order to survive in the IR 4.0 era (Balachandran, 2013) By having high self-efficacy towards ICT make them easier to learn new thing and gain more opportunities in entrepreneurship, which may be helpful for their future entrepreneurial education before starting the process of establishing a business (Todorovic, McNaughton, & Guild, 2011;Yemini & Haddad, 2010).…”
Section: Computer Self-efficacy and Internet Self-efficacymentioning
confidence: 99%